2009
DOI: 10.1007/s11581-009-0385-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, chemical interaction, and conductivity of a PEO-ENR50 based on solid polymer electrolyte

Abstract: A solid polymer electrolytes (SPE) comprising blend of poly(ethylene oxide; PEO) and epoxidized natural rubber as a polymer host and LiCF 3 SO 3 as a dopant were prepared by solution-casting technique. The SPE films were characterized by field emission scanning electron microscopy to determine the surface morphology, X-ray diffraction, and differential scanning calorimeter to determine the crystallinity and thermogravimetric analysis to confirm the mass decrease caused by loss of the solvent. While the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 149 publications
(71 citation statements)
references
References 28 publications
3
68
0
Order By: Relevance
“…The LiBF 4 peaks are not seen in any of the polymer-salt complexes and this signifies that LiBF 4 salt solvates very well in MG49-PMMA matrix, resulting in absence of pure salt phase in the complexes [14]. Fig.…”
Section: Ft-ir Analysismentioning
confidence: 85%
See 2 more Smart Citations
“…The LiBF 4 peaks are not seen in any of the polymer-salt complexes and this signifies that LiBF 4 salt solvates very well in MG49-PMMA matrix, resulting in absence of pure salt phase in the complexes [14]. Fig.…”
Section: Ft-ir Analysismentioning
confidence: 85%
“…It was observed that the vibration mode of v(C-O-C), and (O-CH 3 ) at 984 cm -1 and 1457 cm -1 for pure MG49 were shifted to 992 cm -1 and 1450 cm -1 after blending with PMMA. This shifting was due to existence of intermolecular interaction between oxygen atoms with methylene group in the MMA moiety [14]. With the addition of LiBF 4 salt, the intensity of v(C-O-C), v as (C-O-C) and (O-CH 3 ) of MMA peak was reduced and shifted to lower wavenumbers.…”
Section: Ft-ir Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…The formation of micro-voids over the surface of films is due to rapid evaporation of the solvent during the preparation of polymer blends. Apparently, surface smoothness It evidences for further increase of amorphous portion in the matrix of salt complexed nano composites, which favours for the enhancement of ionic conductivity [38][39][40]. From the TEM image ( figure 2(c)) the average size of nano fillers is found to be 10 nm and dispersed nano particles are observed to be uniformly distributed in the matrix of salt complexed blend electrolytes.…”
Section: Microstructural Propertiesmentioning
confidence: 94%
“…The coordination interactions of the ether oxygen atoms of MAA:EA with VO 2+ cations, which result in a reduction in crystallinity of MAA:EA copolymer, are responsible for the increase in ionic conductivity. The maximum conductivity shows the maximum and effective interaction between oxygen atoms and VO 2+ cations in the electrolytes 19 . VO 2+ ions dissociation is an additional factor in enhancement of ionic conductivity.…”
Section: Composition Dependence Of Conductivitymentioning
confidence: 99%